The Influence Of Leadership Style On The Work Spirit Of Employees In The Production Department Of Pt. Samudra Indonesia - Nurhaedah; Andi Arwinda (IECON: International Economics and Business Conference, 2024)
The Influence of Leadership Style on Employee Work Enthusiasm in the  roduction Department of PT. Samudera Indonesia. This study aims to analyze the influence of leadership style on employee work enthusiasm in the Production Department of PT. Samudera Indonesia. Employee work enthusiasm is an important factor in achieving organizational goals, especially in increasing productivity. The leadership style applied by a leader can be one of the factors influencing employee work motivation. This research uses a quantitative method with a survey approach. The population in this study consists of all employees in the Production Department of PT. Samudera Indonesia, while the sample was taken randomly. Data were collected through questionnaires and then analyzed using simple linear regression analysis. The research results show that there is a significant influence between leadership style and employee work spirit in the Production Department of PT. Samudra Indonesia. This means that the better the leadership style applied, the higher the employees' work enthusiasm will be. The implication of this research is the importance for leaders at PT. Samudera Indonesia to implement effective leadership styles in enhancing employee work motivation